2022
DOI: 10.3168/jds.2021-21325
|View full text |Cite
|
Sign up to set email alerts
|

Changes of antibiotic resistance genes and gut microbiota after the ingestion of goat milk

Abstract: Antibiotic resistance genes, as newly emerging contaminants, have become a serious challenge to public health through the food chain. The gut of humans and animals is an important reservoir for the development and dissemination of antibiotic resistance genes because of the great abundance and diversity of intestinal microbiota. In the present study, we evaluated the influence of goat milk on the diversity and abundance of antibiotic resistance genes and gut microbial communities, especially pathogenic bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Antibiotics are effective in subsets of patients with IBD, and most rodent colitis models suggest that inflammation does not occur in sterile environments [ 73 , 74 ]. However, the gut of humans is an important reservoir for the development of antibiotic resistance genes because of the great abundance and diversity of gut microbiota [ 75 ]. A study performed by Gao and Fan conducted an antibiotic resistance analysis of H. pylori in 365 Chinese people and found that the resistance rates to clarithromycin, amoxicillin, fluoroquinolone, and tetracycline were 65.06%, 7.54%, 61.39%, and 20.37%, respectively [ 76 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics are effective in subsets of patients with IBD, and most rodent colitis models suggest that inflammation does not occur in sterile environments [ 73 , 74 ]. However, the gut of humans is an important reservoir for the development of antibiotic resistance genes because of the great abundance and diversity of gut microbiota [ 75 ]. A study performed by Gao and Fan conducted an antibiotic resistance analysis of H. pylori in 365 Chinese people and found that the resistance rates to clarithromycin, amoxicillin, fluoroquinolone, and tetracycline were 65.06%, 7.54%, 61.39%, and 20.37%, respectively [ 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study performed by Gao and Fan conducted an antibiotic resistance analysis of H. pylori in 365 Chinese people and found that the resistance rates to clarithromycin, amoxicillin, fluoroquinolone, and tetracycline were 65.06%, 7.54%, 61.39%, and 20.37%, respectively [ 76 ]. Interestingly, Liu and Zhang found that goat milk intake might decrease the transfer potential of antibiotic resistance gene to pathogenic bacteria in the gut, thus reducing the abundance of pathogenic bacteria, such as H. bilis [ 75 ]. Therefore, changes in diet may have some therapeutic effect on the antibiotic resistance of pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%